ANALISIS KEGAGALAN GEOMETRI KOMPONEN BRACKET HINGE CAB PADA PROSES BORING DIMESIN CNC MILLING OKK VC51 - Kupainudin; Denny Prumanto; Rani Anggraeny (KALPIKA, 2022)
The Boring Process of Hinge Cab Bracket components is one of the machining processes at PT. MMI.Boring work is the process of enlarging the hole to the desired size and usually pays less attention togeometric deviations from the results of the boring process, even though it greatly affects the quality of themachining results. In general, a spherical profile is said to be perfectly round if the distance of the pointscontained in the geometric shape have the same distance from a point called the center point. The purpose ofthe study was to determine the effect of spindle speed and feeding speed on the geometric size of the barcketcomponent. The method used in this research is an engineering study with experiments and data collection iscarried out through field observations and analysis of ongoing programs. The independent variable in thisstudy was 0.1 mm infeed depth, with spindle rotation parameters of 400 rpm, 500 rpm, 600 rpm, 700 rpmand 800 rpm. The dependent variable is the geometric deviation of the Bracket Hinge Cab boring results.The control variable is the insert type TNMG332-GN LC5010 which has a feed speed (fz) of 0.1 mm/rev anda roughing size of 104 ±0.30, coolant damin water and ecocool 2700T. The measurement method uses a boregauge/cylinder gauge to determine the effect of variations in machining parameters on the geometry of theboring results with a tolerance of ± 0.30 mm and takes 4 axes of measurement, namely X, Y, X', Y'. From theresearch that has been done that the parameter with the smallest geometric deviation is obtained in the fourparts with a spindle rotation (n) 700 rpm, which is the expected result because the geometric deviation is70μm, still within the tolerance limit of ± 0.30 mm and has a roughness level of 9.278 Ra. The greater thevalue of the cutting speed (Vc), the smaller the geometric deviation that occurs. To get good results based onthe analysis and for results that are in accordance with the standard, the best Rpm is used at 700 rpm withFeeding 140 mm/minute.